A NEW SPECIES OF CHLEROGAS FROM THE ANDES OF CENTRAL COLOMBIA (HYMENOPTERA: HALICTIDAE) - Engel M; Gonzalez Victo H (Caldasia)
ABSTRACTA new species of the long-headed bee genus Chlerogas Vachal (Halictinae:Augochlorini) is described and fi gured from a male captured at high elevation in centralColombia. Chlerogas tatamaensis Engel & Gonzalez, new species, is distinguishedfrom its congeners on the basis of integumental coloration and sculpturing as wellas features of the male terminalia. A revised key to the species of Chlerogas isprovided.